Sosialisasi Enam Langkah Cuci Tangan Pada Anak Di SD Negeri 2 Kairatu Pada Masa Pandemi Covid-19 - Suryanti Tukiman (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Washing hands as often as possible and using the six steps for washing children's hands is one of the most important steps to prevent Covid-19 infection in children. Washing your hands with soap is much more effective at killing germs, bacteria and viruses compared to washing your hands using just water. Soap can easily destroy the Covid-19 lipid membrane, making the Covid-19 virus inactive. The aim of this activity is to increase knowledge among elementary school students, by socializing the six steps for washing hands among elementary school children during the Covid-19 pandemic at SD Negeri 2 Kairatu, Kairatu Village. The method for implementing this activity is in the form of health education about six-step hand washing, the benefits of hand washing, and a demonstration of six-step hand washing by grade 3 elementary school students at SD Negeri 2 Kairatu. The results of this community service activity were an increase in children's knowledge regarding the 6 (six) steps for correct hand washing.